Analysis of company operational performance using an entrepreneurial orientation measurement scale (2023)
The purpose of this research is to explore the relationship between entrepreneurial orientation (EO) and performance in Colombian companies. Previous research has shown that the dimensions of EO are positively related to company performance. Although EO models are available and have been validated for other countries, such validation is missing for Colombia. One of the instruments measuring three dimensions and nine variables of EO was applied to a population of 144 company representatives— executives in Cartagena, Colombia. The data was analyzed using structural equation modeling, showing strong internal consistency and construct coherency. The results indicate these Colombian companies— either deliberately or unintentionally—are strongly aligned and derive benefits from EO principles. The contribution of this article is to validate EO for Colombia and encourage further studies of company performance throughout Latin America.